Clinical Characteristics of Sarcoidosis in Asian Population: A 14-year Single Center Retrospective Cohort Study from Thailand - Tripipitsiriwat, Athiwat; Komoltri, Chulaluk; Ruangchira-urai, Ruchira; Ungprasert, Patompong (Sarcoidosis, Vasculitis and Diffuse Lung Diseases, 2020)
Background: Little is known about epidemiology and clinical characteristics of sarcoidosis in Asian population. Objectives: This study aimed to examine the epidemiology and clinical characteristics of Thai patients with sarcoidosis, using databases of a tertiary care medical center. Methods: Potential cases of sarcoidosis were identified from two sources, the medical record-linkage system and the pathology database of Siriraj Hospital, Mahidol University in Bangkok, Thailand. Patients with ICD-10-CM codes for sarcoidosis were identified and retrieved from the medical record-linkage system from 2005 to 2018. Patients with histopathology positive for non-caseating granuloma were identified and retrieved from the pathology database from the same time period. All potential cases underwent individual medical record review to confirm the diagnosis of sarcoidosis which required compatible clinical pictures supported by presence of non-caseating granuloma, radiographic evidence of intrathoracic sarcoidosis and exclusion of other granulomatous diseases. Results: From 2005 to 2018, 89 confirmed cases of sarcoidosis were identified. 80.9% of them were female and mean age at diagnosis was 46.8 years (standard deviation (SD) 13.9 years). The majority of patients had intrathoracic disease (81 cases; 91.0%) but less than half had respiratory symptoms (34 cases; 41.9%). Extrathoracic disease was common in this cohort that pulmonary sarcoidosis was accompanied by extrathoracic involvement in 53 patients (65.4%). Sarcoid uveitis was the most common extrathoracic disease (35 cases; 39.3%), followed by cutaneous sarcoidosis (24 cases; 26.9%), extrathoracic lymphadenopathy (18 cases; 22.5%) and sarcoid arthropathy (4 cases; 4.5%). Conclusion: The current study examined clinical characteristics of sarcoidosis in an Asian population and found high prevalence of uveitis and marked female predominance.